Optimization of Sunscreen Cream Formulation Containing Ethanolic Extract of Avocado Leaves (Persea americana Mill.) or Mangosteen Rind (Garcinia mangostana L.) Combined with Octyl Methoxycinnamate: Optimasi Formula Krim Tabir Surya Mengandung Ekstrak Etanolik Daun Alpukat (Persea americana Mill.) atau Kulit Manggis (Garcinia mangostana L.) Kombinasi dengan Oktil Metoksisinamat - Verda, Vanessia; Leonardo, William; Prismawan, Deka; Notario, Dion (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Most sunscreens contain chemicals that can cause health and environmental problems. Natural actives can be an alternative to minimize the use of chemicals. Avocado leaves (Persea americana Mill.) and mangosteen peel (Garcinia mangostana L.) contain active compounds that have UV absorption. Objective: In this study, the optimal composition of a mixture of ethanol extracts of avocado leaves or mangosteen peel with octyl methoxycinnamate (OMC) was determined based on the Sun Protection Factor (SPF) and adhesive properties using Response Surface Methodology (RSM). Material and method: The optimal formula calculated with RSM was then made and underwent a series of tests, including a hedonic test with a scale of 0-9 on 30 respondents, a freeze-thaw stability test, and an accelerated stability test with the Arrhenius equation. Results: The RSM analysis showed that the optimal concentration of extract and OMC was 10% and 0.75% (avocado leaves) & 0.65% (mangosteen peel). The optimized formula resulted in adhesive properties and SPF of 7.41±0.03 and 16.52±0.16 (avocado leaves) & 7.43±0.04 and 15.84±0.15 (mangosteen peel) respectively. Both optimized formulations were physically stable against freeze-thaw and had a t90 of 29 minutes (avocado leaves) and 17 minutes (mangosteen peel). The average hedonic scale obtained was 7.8 (avocado leaves) and 7.9 (mangosteen peel), indicating that both optimized formulations were preferred by the respondents. Conclusions: The sunscreen formulation with an optimized combination of active ingredients from avocado leaf extract or mangosteen peel extract with OMC using RSM results in preparation with SPF value and physical properties that meet the requirements.